WEAVING IDEOLOGY THROUGH WORDS: THE ROLE OF METAPHORS IN THE NDC 2020 MANIFESTO - Nkrumah, Edward (Universitas Islam Sumatera Utara (UISU), 2025)
Metaphors are significant rhetorical tools that shape public perception and construct political identities (Charteris-Black, 2014). This study examines how metaphorical framing functions as an ideological instrument in the National Democratic Congress’s (NDC) 2020 manifesto. It aims at uncovering how metaphorical framing functions as an ideological tool in political discourse. Using a descriptive content analysis and qualitative interpretive research design grounded in a Critical Metaphor Analysis (CMA) approach, the study identifies five dominant metaphorical constructs—building (most prevalent), growth, journey, war, and health metaphors—each serving distinct rhetorical purposes. Additionally, the study reveals five key ideological functions of metaphor in the manifesto: constructing legitimacy, projecting development and vitality, naturalizing crisis and delegitimizing the incumbent, mobilizing collective identity, and contesting power and framing opposition. The study provides unique insight into how opposition parties in African democracies strategically deploy metaphorical language in manifestos to critique incumbents, frame alternative visions, and mobilize public support.